Jamaica : Toward a Strategy for Financial Weather Risk Management in Agriculture - World Bank (Washington, DC, 2013)
This report forms part of the technical assistance provided by the World Bank under the Non-lending Technical Assistance Program for the Caribbean 'market-based agriculture risk management in the Caribbean.' The program is largely financed by the European Union All Agriculture Commodities Program (AACP) Initiative and contributions from the International Fund for Agriculture Development (IFAD) and the World Bank. This document provides technical input for designing a national strategy for addressing the financial weather risks facing the agricultural sector of Jamaica. As such, it identifies the various options from current available financial risk transfer instruments for addressing crop weather risks for small farmers (livestock risks are not directly addressed in this report) and identifies the public investments needed for supporting market development of the agricultural insurance market. The report is structured in five sections to facilitate its presentation. The first two sections present a snapshot of the Jamaican economy and agricultural sector, and the current situation of agricultural insurance; third section addresses a set of key issues for designing a government strategy for agricultural financial weather risk management; fourth section contains the elements of public policy and investments to support market development for agricultural insurance, and various illustrations of how to structure financial weather risk management instruments for the sector. The report concludes with a short section containing final remarks and recommendations.